The decommissioning challenge - Liew, M.S. (Society of Naval Architects and Marine Engineers, 2015)
A number of challenges and opportunities for decommissioning were identified in the ASEAN countries at the Association of South East Asian Nations (ASEAN) Council on Petroleum (ASCOPE) Conference in 2001. Decommissioning global business value is a huge, billion dollar market due to the increasing number of aging fields and off shore platforms. In the ASEAN countries, regulations related to decommissioning, or rather a lack of them, contributes to the delay of decommissioning activities taking place in the host country. In Malaysia, as the custodian and statutory manager of national petroleum resources, PETRONAS is obligated to address the process of decommissioning consistent with national laws and international conventions. The main guiding document for decommissioning activities in Malaysia is the PETRONAS Procedures and Guidelines for Upstream Activities (PPGUA). The key challenges for decommissioning in Malaysia are lack of experience and therefore in-depth knowledge and expertise in this area. Innovation in technology and strategies could be important emerging challenges that drive decommissioning. Having the right technology to address the right tasks is crucial in ensuring on time project delivery. The O&G industry has its own set of persistent and continuously emerging challenges that drive change.